Implementing core NICE guidelines for osteoarthritis in primary care with a model consultation (MOSAICS): a cluster randomised controlled trial. Issue 1 (January 2018) - Dziedzic, K.S.; Healey, E.L.; Porcheret, M.; Afolabi, E.K.; Lewis, M.; Morden, A.; Jinks, C.; McHugh, G.A.; Ryan, S.; Finney, A.; Main, C.; Edwards, J.J.; et al.
Summary: Objective: To determine the effectiveness of a model osteoarthritis consultation, compared with usual care, on physical function and uptake of National Institute for Health and Care Excellence (NICE) osteoarthritis recommendations, in adults ≥45 years consulting with peripheral joint pain in UK general practice. Method: Two-arm cluster-randomised controlled trial with baseline health survey. Eight general practices in England. Participants: 525 adults ≥45 years consulting for peripheral joint pain, amongst 28, 443 population survey recipients. Four intervention practices delivered the model osteoarthritis consultation to patients consulting with peripheral joint pain; four control practices continued usual care. The primary clinical outcome of the trial was the SF-12 physical component score (PCS) at 6 months; the main secondary outcome was uptake of NICE core recommendations by 6 months, measured by osteoarthritis quality indicators. A Linear Mixed Model was used to analyse clinical outcome data (SF-12 PCS). Differences in quality indicator outcomes were assessed using logistic regression. Results: 525 eligible participants were enrolled (mean age 67.3 years, SD 10.5; 59.6% female): 288 from intervention and 237 from control practices. There were no statistically significant differences in SF-12 PCS: mean difference at the 6-month primary endpoint was −0.37 (95% CI −2.32, 1.57). Uptake of core NICE recommendations by 6 months was statistically significantly higher in the intervention arm compared with control: e.g., increased written exercise information, 20.5% (7.9, 28.3). Conclusion: Whilst uptake of core NICE recommendations was increased, there was no evidence of benefit of this intervention, as delivered in this pragmatic randomised trial, on the primary outcome of physical functioning at 6 months. Trial registration: ISRCTN06984617.